The last century of Lao royalty a documentary history - Evans, Grant 1948- (Silkworm Books, 2009)
Lao royalty's engagement in all the major events of the country in the last century forms a rich and complex narrative. But with the 1975 Communist revolution this history fell into oblivion and has all but disappeared from public memory. The Last Century of Lao Royalty recovers this history by presenting a wealth of rare documents and photographs. They bring to life the political, social, and cultural activities of the members of the royal families and provide a unique perspective on the role of royalty in modern Laos. Royalty was, in fact, a force for moderation, modernization, and democracy during the period of the Royal Lao Government (1947-1975). The last king, King Sisavang Vatthana, for instance, refused to give his imprimatur to a military dictatorship because he was so doggedly committed to constitutional rule.